2017
DOI: 10.2105/ajph.2017.303922
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Health Conditions and Key Health Indicators Among Lesbian, Gay, and Bisexual Older US Adults, 2013–2014

Abstract: Objectives To examine disparities in chronic conditions and health indicators among lesbian, gay, and bisexual (LGB) adults aged 50 years or older in the United States. Methods We used data from the 2013 and 2014 National Health Interview Survey to compare disparities in chronic conditions, health outcomes and behaviors, health care access, and preventive health care by sexual orientation and gender. Results LGB older adults were significantly more likely than heterosexual older adults to have a weakened i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 22 publications
6
131
0
Order By: Relevance
“…Among sexual minority men, evidence suggests that they are at increased risk for the following health conditions relative to heterosexual men: angina pectoris (Fredriksen-Goldsen et al, 2017), arthritis (Fredriksen-Goldsen, Kim, Barkan, Muraco, & Hoy-Ellis, 2013), diabetes (Conron, Mimiaga, & Landers, 2010; Wallace, Cochran, Durazo, & Ford, 2011), cardiovascular disease (Blosnich et al, 2016; Cochran & Mays, 2007; Hatzenbuehler, McLaughlin, & Slopen, 2013), hypertension (Cochran & Mays, 2007; Everett & Mollborn, 2013; Wallace et al, 2011) and high blood pressure (Hatzenbuehler et al, 2013), hepatic disease, gastrointestinal problems (Cochran & Mays, 2007), stroke (Blosnich et al, 2016), and being underweight (Laska et al, 2015). Studies have similarly indicated differential risk for gay and bisexual men; for instance, bisexual men are at increased risk for diabetes relative to gay men (Fredriksen-Goldsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among sexual minority men, evidence suggests that they are at increased risk for the following health conditions relative to heterosexual men: angina pectoris (Fredriksen-Goldsen et al, 2017), arthritis (Fredriksen-Goldsen, Kim, Barkan, Muraco, & Hoy-Ellis, 2013), diabetes (Conron, Mimiaga, & Landers, 2010; Wallace, Cochran, Durazo, & Ford, 2011), cardiovascular disease (Blosnich et al, 2016; Cochran & Mays, 2007; Hatzenbuehler, McLaughlin, & Slopen, 2013), hypertension (Cochran & Mays, 2007; Everett & Mollborn, 2013; Wallace et al, 2011) and high blood pressure (Hatzenbuehler et al, 2013), hepatic disease, gastrointestinal problems (Cochran & Mays, 2007), stroke (Blosnich et al, 2016), and being underweight (Laska et al, 2015). Studies have similarly indicated differential risk for gay and bisexual men; for instance, bisexual men are at increased risk for diabetes relative to gay men (Fredriksen-Goldsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the link between migraine and smoking status may be contingent on past or present daily smoking as opposed to less frequent, occasional smoking. 49 In addition, a national study of the Dutch population found that gay men were more likely to report migraine or severe headache, compared to heterosexual men. 15,47 Physical and mental health disparities among aging sexual minority communities, including chronic conditions, have been documented in the Washington State Behavioral Risk Factor Surveillance System 48 and National Health Interview Survey.…”
Section: Discussionmentioning
confidence: 99%
“…15,47 Physical and mental health disparities among aging sexual minority communities, including chronic conditions, have been documented in the Washington State Behavioral Risk Factor Surveillance System 48 and National Health Interview Survey. 49 In addition, a national study of the Dutch population found that gay men were more likely to report migraine or severe headache, compared to heterosexual men. 47 Similarly, we found an association between migraine and gay and bisexual identities for men, but not lesbian and bisexual women, a result that corresponds with findings from California.…”
Section: Discussionmentioning
confidence: 99%
“…A convergence of findings across studies now documents health disparities specific to lesbian, gay, bisexual, and transgender people, 7 including elevated rates of disability, poor physical health, and mental distress among older adults. [8][9][10] Based on the first national probability study of lesbian, gay, and bisexual older adult health, using multi-year data from the National Health Interview Survey (NHIS), 11 we found that lesbian, gay, and bisexual adults aged 50 and older, compared with their heterosexual counterparts, had higher rates of 9 out of 12 chronic conditions. Lesbian and bisexual older women reported greater prevalence of arthritis, asthma, heart attack, stroke, and multiple chronic conditions and poor general health, than heterosexual older women.…”
Section: Translational Research: Investigating Health Disparitiesmentioning
confidence: 99%
“…17 Replication studies are now needed to validate the evidence of health disparities, particularly these newly observed findings in chronic health conditions and subgroup differences. 11 However, most population-based health and aging studies have not incorporated sexual orientation and gender identity and expression measures, and if they have, small sample sizes of LGBTQ older adults, particularly subgroups (e.g., racial and ethnic minorities, transgender older adults, the oldest old), remain a major concern. Queer-identified older adults are another subgroup that needs more attention in future health disparity research as little is known about the demographics of this population as well as their health and quality of life.…”
Section: Translational Research: Investigating Health Disparitiesmentioning
confidence: 99%